Frustrated Caring: Family Members’ Experience of Motivating COPD Patients Towards Self-Management - Sigurgeirsdottir,Jonina; Halldorsdottir,Sigridur; Arnardottir,Ragnheidur Harpa; Gudmundsson,Gunnar; Bjornsson,Eythor Hreinn (International Journal of Chronic Obstructive Pulmonary Disease, 2020)
Jonina Sigurgeirsdottir,1,2 Sigridur Halldorsdottir,3 Ragnheidur Harpa Arnardottir,3– 5 Gunnar Gudmundsson,1,6 Eythor Hreinn Bjornsson2 1University of Iceland, Medical Faculty, Reykjavik, Iceland; 2Reykjalundur Rehabilitation Center, Lung Department, Mosfellsbaer, Iceland; 3University of Akureyri, School of Health Sciences, Faculty of Graduate Studies, Akureyri, Iceland; 4Akureyri Hospital, Department of Rehabilitation, Akureyri, Iceland; 5Uppsala University, Department of Medical Sciences, Respiratory-, Allergy- and Sleep Research, Uppsala, Sweden; 6Landspitali University Hospital, Department of Respiratory Medicine, Reykjavik, IcelandCorrespondence: Jonina SigurgeirsdottirReykjalundur Rehabilitation Center, Lung Department, Mosfellsbaer 270, IcelandTel +354 6261740Email jonina@reykjalundur.isAim: The aim of this phenomenological study was to explore principal family members’ experience of motivating patients with chronic obstructive pulmonary disease (COPD) towards self-management.Methods: Interviews were conducted with 10 family members (spouses and adult children) of COPD patients. The interviews were audio recorded, transcribed and analyzed thematically.Results: Being a principal family member of a COPD patient is characterized by frustrated caring; wanting the best for him/her and yet carrying a heavier burden than the person feels equipped for, lacking both knowledge about the disease progress and information about available healthcare resources. The situation demands much energy, due to COPD patients’ lack of stamina; family members’ fear of the patient’s possible breathlessness; willingness to help, though sometimes meeting with negative reactions from the patient; and feeling ignored by health professionals (HPs). Family members expressed a need for a formal connection between patient–family–HPs. The increasing burden experienced by patients’ family members is characterized by a sequential process in three phases of the patient’s declining self-management. In the early phase, family and patient are ...